Insights into Electrolytic Pre‐Lithiation: A Thorough Analysis Using Silicon Thin Film Anodes. Issue 8 (11th December 2022) - Haneke, Lukas; Pfeiffer, Felix; Bärmann, Peer; Wrogemann, Jens; Peschel, Christoph; Neumann, Jonas; Kux, Fabian; Nowak, Sascha; Winter, Martin; Placke, Tobias
Abstract: Pre‐lithiation via electrolysis, herein defined as electrolytic pre‐lithiation, using cost‐efficient electrolytes based on lithium chloride (LiCl), is successfully demonstrated as a proof‐of‐concept for enabling lithium‐ion battery full‐cells with high silicon content negative electrodes. An electrolyte for pre‐lithiation based on γ‐butyrolactone and LiCl is optimized using boron‐containing additives (lithium bis(oxalato)borate, lithium difluoro(oxalate)borate) and CO2 with respect to the formation of a protective solid electrolyte interphase (SEI) on silicon thin films as model electrodes. Reversible lithiation in Si||Li metal cells is demonstrated with Coulombic efficiencies ( C Eff ) of 95–96% for optimized electrolytes comparable to 1 m LiPF6 /EC:EMC 3:7. Formation of an effective SEI is shown by cyclic voltammetry and X‐ray photoelectron spectroscopy (XPS). electrolytic pre‐lithiation experiments show that notable amounts of the gaseous product Cl2 dissolve in the electrolyte leading to a self‐discharge Cl2 /Cl − shuttle mechanism between the electrodes lowering pre‐lithiation efficiency and causing current collector corrosion. However, no significant degradation of the Si active material and the SEI due to contact with elemental chlorine is found by SEM, impedance, and XPS. In NCM111||Si full‐cells, the capacity retention in the 100th cycle can be significantly increased from 54% to 78% by electrolytic pre‐lithiation, compared to reference cells without pre‐lithiation of Si. Abstract : Pre‐lithiation is a promising approach to enable the application of anodes with high Si content for lithium‐ion batteries. Here, an alternative electrochemical pre‐lithiation method based on the electrolysis of lithium chloride is investigated. The electrolyte is optimized and investigated regarding solid electrolyte interphase formation on Si thin films. Lab‐scale application of the electrolytic pre‐lithiation approach is critically discussed.